Cheney the untold story of America's most powerful and controversial vice president - Hayes, Stephen F. (HarperCollins, 2007)
During a forty-year career in politics, Vice President Dick Cheney has been involved in some of the most consequential decisions in recent American history. Yet for all of his influence, the world knows very little about the most powerful vice president in U.S. history, among the most secretive and guarded of all public officials. Journalist Hayes draws upon hundreds of interviews with the vice president, his boyhood friends, political mentors, family members, reticent staffers, and senior Bush administration officials, to deliver a comprehensive portrait. The topics covered include Cheney's withdrawal from Yale; his days in the Ford White House; his meteoric rise to congressional leadership; his opposition to removing Saddam Hussein from power after the first Gulf War; his selection as Bush's running mate; his performance on 9/11 and the aggressive measures he pushed in the aftermath; the Iraq War; and intelligence battles with the CIA and their lasting effects.--From publisher description.